Histopathological Difference of Inflammatory Cells Infiltration into Fetal Membranes of PROM and Non-PROM - SUDIARTA, KETUT EDY; FABIOLLA, FABIOLLA; HERDIYANTINI, MITA (Nusantara Medical Science Journal, 2025)
Introduction: Premature rupture of membranes (PROM) remains one of several causes of premature birth that increases both maternal mortality ratio and neonatal mortality rate. Inflammation of fetal membranes leads to release of inflammatory mediators and resulting in weakness of fetal membranes, particularly the amniotic membrane. The amniotic membrane in PROM has a focal weakness, which differs from the membrane in non-premature rupture of membrane (non-PROM) that has a generalized weakness. This research aimed to determine histopathological difference of inflammatory cells infiltration into fetal membranes of PROM and non-PROM.   Methods:  Quantitative observation was applied to this research. Cross-sectional design was used for analyzing data. Primary data was collected from the delivery room and operating theater of Emergency Department in dr. Ramelan Central Naval Hospital (RSPAL dr. Ramelan) Surabaya. Data collection started from August to November 2019 using total population sampling technique. Results: A total of 40 samples histopathologically examined showed that 11 out of 20 (55%) fetal membranes in PROM had polymorphonuclear (PMN) cells infiltration and 9 (45%) did not have PMN cells infiltration, 1 out of 20 (5%) fetal membranes in non-PROM had PMN cells infiltration and 19 (95%) did not have PMN cells infiltration. The prevalence ratio (PR) of PROM based upon the presence of PMN cells infiltration into fetal membranes was 2.85 (PR>1). The significance level of Chi-square test was 0.001 (ρ>0.05). Conclusions: The difference of inflammatory cells infiltration into fetal membranes of PROM and non-PROM was statistically significant.